Combination therapy in hypertension - Brian Rayner (South African Family Practice)
Hypertension is one of the most important risk factors for death, heart failure, ischaemic heart disease, stroke and chronic kidney disease. Treatment of hypertension to particularly to goal blood pressure (BP) prevents these complications. In South Africa the reported control rates for treated hypertensives using a goal BP 140/90 mm Hg is about 40%. Control of hypertension remains an elusive goal. The reasons for this are complex, but doctor inertia is emerging as an important barrier to better control rates.